Lon protease negatively affects GacA protein stability and expression of the Gac/Rsm signal transduction pathway in Pseudomonas protegens. (18th February 2014) - Takeuchi, Kasumi; Tsuchiya, Wataru; Noda, Naomi; Suzuki, Rintaro; Yamazaki, Toshimasa; Haas, Dieter
Summary In Pseudomonas protegens CHA0 and other fluorescent pseudomonads, the Gac/Rsm signal transduction pathway controls secondary metabolism and suppression of fungal root pathogens via the expression of regulatory small RNAs (sRNAs). Because of its high cost, this pathway needs to be protected from overexpression and to be turned off in response to environmental stress such as the lack of nutrients. However, little is known about its underlying molecular mechanisms. In this study, we demonstrated that Lon protease, a member of the ATP‐dependent protease family, negatively regulated the Gac/Rsm cascade. In a lon mutant, the steady‐state levels and the stability of the GacA protein were significantly elevated at the end of exponential growth. As a consequence, the expression of the sRNAs RsmY and RsmZ and that of dependent physiological functions such as antibiotic production were significantly enhanced. Biocontrol of Pythium ultimum on cucumber roots required fewer lon mutant cells than wild‐type cells. In starved cells, the loss of Lon function prolonged the half‐life of the GacA protein. Thus, Lon protease is an important negative regulator of the Gac/Rsm signal transduction pathway in P. protegens.